The Effect of Relationship Marketing, Experential Marketing and Sharia Marketing Characteristics on Customer Loyalty of Sharia Bank With Customer Satisfaction as Intervening Variable - Priantoro, Maulana Agung; Yudiana, Fetria Eka (MALIA: Journal of Islamic Banking and Finance, 2021)
Loyalty is a consumer's commitment to a business model that can be in the form of a brand, store, and/or supplier due to several things that cause consumers to make long-term purchases. The data was obtained from the distribution of questionnaires by researchers to respondents. Samples were taken as many as 100 respondents. Data collection techniques by non-probability sampling. The data obtained were then processed using the SPSS20 tool. This research uses quantitative research by using multiple linear regression analysis and path analysis..The results of this study indicate that the Relationship Marketing variable has a negative and insignificant effect on Loyalty. The Experiential Marketing variable has a positive and insignificant effect on Loyalty, the Characteristics Variable of Sharia Marketing has a positive and significant effect on Loyalty. Then the Satisfaction variable has a positive and insignificant effect on Loyalty. Furthermore, the Relationship Marketing variable has a positive and significant effect on satisfaction. Furthermore, the Experiential Marketing variable has a positive and significant effect on Satisfaction, the Characteristics Variable of Sharia Marketing has a positive and insignificant effect on Satisfaction, Furthermore, Satisfaction is not able to mediate the influence of Relationship Marketing on Loyalty, the Satisfaction Variable can mediate the influence of Experiential Marketing on Loyalty, and the last variable Satisfaction is able to mediate the influence of the characteristics of Sharia Marketing on Loyalty.